Pemilihan Supplier Obat yang Tepat Menggunakan Metode Multi Attribut Utility Theory - Djasmayena, Selvia; Yunus, Yuhandri; Putra, Rezi Elsya (SEULANGA SYSTEM PUBLISHER, 2019)
Drug suppliers are those who sell and distribute drugs to pharmacies or sections that carry out pharmaceutical activities. Selection of the right supplier can support the operational activities of the pharmacy. Pharmacists must know the right criteria in choosing a supplier. Criteria determined by pharmacies not all suppliers can fulfill it. Overcoming this decision support system is very necessary in the selection of suppliers. Multi-Attribute Utility Theory is a ranking method that helps in supporting supplier selection decisions at Pekanbaru Assyafni Pharmacy. Supplier selection uses 15 sample supplier data and 5 criterion data used as a basis for supplier selection. Such as drug production, delivery time, quality stability, service response, and guarantee. The results of the study get a high degree of accuracy that is 86.67% of the right suppliers and in accordance with the realization of test data. So this research is very important in choosing the right supplier.